Use of coordination spheres in food economics - Tóth, József (Applied Studies in Agribusiness and Commerce, 2009)
The coordination plays central role in the economics. The conventional economic theory looks at the market and enterprise (or hierarchy) as two different, separated manner of coordination of economic goods and services. However the modern organization theory, price theory and institutional economics show that different types (not only market and enterprise, but also several types of hybrid forms) of coordination (or governance structure) necessarily live together in the current economic system. Based on my previous research on the field of regional clusters in the food industry I came to the conclusion that the cluster is one of the spheres where economic coordination can occur.At the same time I pointed out that the ways of coordination can be ordered on an ordinary scale according to its normative or positive nature. I’ve also found that the choice between the coordination spheres (market, enterprise or cluster) is not arbitrary, but instead depends on the interest’s dimension which is represented by the exchange of goods and services in question.